INTERNET-BASED COGNITIVE BEHAVIORAL THERAPY FOR SOMATIC SYMPTOM DISORDER - Ariyanti, Nyoman Triska (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – Somatic symptom disorder (SSD), before known as somatoform disorder (SD), is characterized by a preoccupation that is nondelusional and general with fears of having, or the idea that the body has a serious disease based on his or her misinterpretation of bodily symptoms in six or more months. In SSD management there is a multifaceted approach that is tailored to each patient. Psychological interventions specifically cognitive behavioral therapy reported can improve the symptoms and reduce the healthcare cost significantly. Internet-delivered cognitive behavior therapy (ICBT) has an accepted evidence base for a range of psychiatric problems, especially for SSD treatment also has been suggested as one possible approach that could adapted to this situation. Methods – In this article, researchers used the review method by collecting several kinds of literature from 2011-2021 that discuss somatic symptom disorder, cognitive behavioral therapy, and internet-based cognitive behavioral therapy for somatic symptom disorder. Results – A referral system for patients with SSD to a mental health expert is needed if they do not find any progress when handled by the physician in primary care. Proven therapies for SSD such as CBT and mindfulness-based therapy. ICBT was approved and increased usage within the pandemic of COVID-19 and brought some highly standardized courses consistent across patients. Discuss – The effectiveness of ICBT has been evaluated in the management of generalized anxiety disorder (GAD), depression, panic disorder, post-traumatic stress disorder (PTSD), obsessive-compulsive disorder (OCD), adjustment disorder, chronic pain, bipolar disorder, and phobias. CBT in multicenter randomized controlled trials reported effectiveness in the treatment of SSD and medically unexplained symptoms, “Health anxious” patients get over two years of sustained symptomatic benefit, without any different impact on total costs, and also decreased the physical symptoms, disability, and psychological distress. Conclusion – Internet-based Cognitive Behavioral Therapy (ICBT) can be highly effective in the treatment of somatic symptom disorder (SSD). ICBT can provided in therapist-guided, unguided, or as a bibliotherapy. This tool is already recommended as a treatment of choice during the pandemic. Although wider RCT on the use of ICBT in clinical practice, particularly in SSD therapy, with a variety of demographic characteristics to provide additional evidence of the effectiveness of this technique, as well as increased awareness among clinicians and the general public. Keywords: SSD, somatic, CBT.